Pengaruh Ekstrak Tamarindus indica Terhadap Kenaikan Berat Badan Pada Tikus Rattus norvegicus Yang Diberi Diet Obesitas - Candra Rini Hasanah Putri; Titiek Sunaryati (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2017)
Obesity is a health problem whose prevalence tends to increase in Indonesia. Obesity becomes a concern, because it is one of the parameters that often followed by impaired of glucose tolerance in the metabolic syndrome. In Indonesia, Tamarindus indica is believed as a body slimming substance so it has possibility to become an alternative therapy that is easily available and cheap for obesity. The purpose of this study was to determine the ability of Tamarindus indica in inhibiting obesity. This experiment used 28 male Wistar strains in 2-3 months age that were divided into groups: group 1 (negative control, normal diet without Tamarindus indica), group 2 (positive control, obese diet without Tamarindus indica), group 3 (obese diet + Tamarindus indica 2700mg/kg BW), and group 4 (obese diet + Tamarindus indica 3600mg/kg BW). Measurement were performed in the first day after acclimization before treatment (day 8), and repeated weekly afterwards, ie at day 15, 22, 29, 36, and 43. Anova and Tukey Simultaneous statistics test were performed to see the differences in wight gain per week compared with the first week of study, then compared between groups.  Furthermore, a virtual screening that called insilico bioinformatics analyzes was performed to test the binding activity between quercetin and rutin (compounds in Tamarindus indica) with fatty acid synthase, an enzym that plays a role in de novo synthesis of fatty acids. Tamarindus indica was shown to significantly inhibit weight gain in rats with obese diet food (P=0.000), but differences dose of Tamarindus indica did not appear to have significant effect to inhibit obesity (P=0.321). The ability of Tamarindus indica is due to the compounds quercetin and rutin, where these two ingredients estimated to have the ability to inhibit fatty acid synthase with high strength.